2023
DOI: 10.1029/2023ja031864
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Super Bubbles Near Sunset and Sunrise During the 26–28 February 2023 Geomagnetic Storm

Wenjie Sun,
Guozhu Li,
Jiuhou Lei
et al.

Abstract: Ionospheric equatorial plasma bubbles (EPBs) are usually generated around sunset over equatorial to low latitudes. In this study, super EPBs extending to middle latitudes were observed, which were freshly generated at both post‐sunset and near‐sunrise periods over East/Southeast Asia during the geomagnetic storm on 26–28 February 2023. The post‐sunset (near‐sunrise) EPB persisted ∼4 (8) hours, drifting eastward (westward) and extending up to ∼35°N. Strong L‐band scintillations, deep total electron content (TEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…Recent studies have incorporated multi-instrument observations to analyze the ionospheric irregularities induced by geomagnetic storms. The use of ground-and space-based observables can cross-validate the results from various atmospheric layers [13,21,32]. In addition, electron density measurements of F-layer, assimilation of magnetometer data, satellite-derived thermospheric O/N 2 and the neutral wind observations from Fabry-Perot interferometers (FPIs) have enabled to study the ionospheric-thermospheric coupling in detail [33,34].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have incorporated multi-instrument observations to analyze the ionospheric irregularities induced by geomagnetic storms. The use of ground-and space-based observables can cross-validate the results from various atmospheric layers [13,21,32]. In addition, electron density measurements of F-layer, assimilation of magnetometer data, satellite-derived thermospheric O/N 2 and the neutral wind observations from Fabry-Perot interferometers (FPIs) have enabled to study the ionospheric-thermospheric coupling in detail [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Abdu [12] reported that the growth rate of R-T instability is enhanced/decreased due to the variations in equatorial E region electric fields during different phases of the geomagnetic storms. The enhanced pre-sunset eastward electric fields play a major role in the uplifting of ionospheric plasma, instigating (increasing ionospheric heights, hmF2) the formation of post-sunset equatorial plasma bubbles (EPBs) reaching up to higher latitudes ( [13], and references therein). Although, during the high solar activity periods and equinox season, post-sunset EPBs are common in the American and Asian sectors [14][15][16], nevertheless, the irregularity is confined to equatorial latitudes under normal conditions [13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations